2011
DOI: 10.1021/nl200928k
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Dynamics of Nanoparticle Channelling in Suspended Graphene

Abstract: We have observed a previously undescribed stepwise oxidation of mono- and few layer suspended graphene by silver nanoparticles in situ at subnanometer scale in an environmental transmission electron microscope. Over the range of 600-850 K, we observe crystallographically oriented channelling with rates in the range 0.01-1 nm/s and calculate an activation energy of 0.557 ± 0.016 eV. We present a discrete statistical model for this process and discuss the implications for accurate nanoscale patterning of nanosca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(77 citation statements)
references
References 25 publications
(35 reference statements)
6
70
1
Order By: Relevance
“…Upon temperature increase to 735 °C the particles Forma Forma were found to move parallel to the graphite surface, digging relatively straight channels with sudden change of direction by 60 and 120° [43]. In a similar experiment, between 327 -577 °C and in an atmosphere of 4.5 -13 Pa O2, silver nanoparticles deposited on graphene were reported to catalytically remove carbon atoms producing channels aligned parallel to the <100> graphene directions [45]. This channeling effect could be explained by taking the adhesion energy between the metal particle and the carbon edge atoms in contact with it into consideration.…”
Section: Origin Of Silver Mobility and Its Implications On Catalytic mentioning
confidence: 84%
“…Upon temperature increase to 735 °C the particles Forma Forma were found to move parallel to the graphite surface, digging relatively straight channels with sudden change of direction by 60 and 120° [43]. In a similar experiment, between 327 -577 °C and in an atmosphere of 4.5 -13 Pa O2, silver nanoparticles deposited on graphene were reported to catalytically remove carbon atoms producing channels aligned parallel to the <100> graphene directions [45]. This channeling effect could be explained by taking the adhesion energy between the metal particle and the carbon edge atoms in contact with it into consideration.…”
Section: Origin Of Silver Mobility and Its Implications On Catalytic mentioning
confidence: 84%
“…It is also important to note that the amount of sp² carbon increases in the basal region of the particles. Defects in sp 2 carbon structure occurring at the base of the particle could be explained by the metal catalysed oxidation of carbon [40,41,44,45]. This phenomenon could occur during the cooling step in helium gas containing oxygen traces since iron-based particles are converted into iron oxide particles.…”
Section: Methodsmentioning
confidence: 99%
“…According to the studies reported in the literature, air oxidation involves that a part of carbon atoms bindings with oxygen atoms leaves the sample in form of carbon monoxide or dioxide, creating vacancies in the carbon shells which serves as channels for outward diffusion of metallic core and penetration of oxygen in the interior, thus creating large size hollow Fe 2 O 3 /C ox nanoparticles [40,41,44,45]. However, in our study we could not identify neither hollow particle by electron microscopy nor carbon-oxygen bonding by Raman spectroscopy.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, aberration-corrected HRTEM has been successfully combined with ab initio calculations to study the binding sites and energies of single atoms on graphene (Meyer et al, 2008;Boukhvalov and Katsnelson, 2009;Cretu et al, 2010;Vanin et al, 2010;Zan et al, 2012;Ramasse et al, 2012;Wang et al, 2012aWang et al, , 2012bWang et al, , 2013Hardcastle et al, 2013), Ostwald ripening between mono-and bi-metallic nanoparticles on a-C (Yoshida et al, 2012Alloyeau et al, 2012), the diffusion of metal atoms and clusters on a-C, graphene and C nanotubes (Werner et al, 2005;Wanner et al, 2006;Batson, 2008;Gan et al, 2008;Cretu et al, 2010Cretu et al, , 2012 and the diffusion and etching of clusters on graphene (Booth et al, 2011;Wang et al,2012bWang et al, , 2013. Aberration-corrected HRTEM and density functional theory have also been used to investigate the structures of thiol-protected clusters (Mariscal et al, 2010).…”
Section: Introductionmentioning
confidence: 99%